Experimental Analysis of Heat and Flow Characteristics on Inclined and Multiple Impingement Jet Heat Transfer Using Optimized Heat Sink - Altug Karabey; Dogan Yorulmaz (Applied Sciences)
Thermal management at a high heat flux is crucial for electronic devices, and jet impingement cooling is a promising solution. The heat transfer properties of a rectangular-finned heat sink are investigated under angled and multi-impingement jet configurations in this study. Experiments were conducted with three different nozzle diameters, three different heat sink angles, three dimensionless nozzle-to-heat sink distance ratios, and five different velocity values. As a result, the obtained data are presented as Nu-Re graphs, and the impacts of the parameters on heat transfer (HT) are analyzed. It is concluded that the Nusselt number increases with the increasing nozzle diameter and Reynolds number, whereas it decreases with increasing distance between the nozzle and the heat sink. When comparing the angle values under an identical flow velocity, nozzle diameter, and dimensionless h/d distance experimental conditions, it was found that the Nusselt numbers were very close to each other. Under constant heat flux and for all investigated angles, the highest Nusselt number for the rectangular-finned inclined heat sink was observed at a 10° heat sink inclination, a nozzle diameter of D = 40 mm, a dimensionless distance of h/d = 6, and a flow velocity of 9 m/s. This study deepens the understanding of the heat transfer mechanism of impinging jets and provides an efficient method framework for practical applications.